Impact of all-oral bedaquiline-based shorter regimens in the treatment of drug-resistant tuberculosis: a systematic review and meta-analysis - Ming Liu; Lianping Yang; Shanquan Chen; Yan He; Nathorn Chaiyakunapruk; Wai-kit Ming; Jing Yu; Tesfaye Regassa Feyissa; Xiaohan Chen; Getahun Fetensa; Ebisa Turi; Ginenus Fekadu; et al. (BMJ Global Health)
Background Drug-resistant tuberculosis (DR-TB) presents a significant global obstacle to TB control efforts, necessitating improved intervention strategies. The introduction of potent drugs, such as bedaquiline (Bdq), has led to the development of shorter treatment regimens. This systematic review and meta-analysis aimed to examine the impact of these regimens, synthesising data from recent clinical trials and observational studies.Methods We searched multiple databases, including Medline and Scopus, for studies published from 2012 to February 2024. Eligible studies included clinical trials and cohort studies involving adults diagnosed with DR-TB treated with Bdq-based all-oral regimens lasting up to 12 months. Primary outcomes were treatment success rate (TSR) and incidence of serious adverse events (SAEs). We also compared efficacy and safety with longer oral or injectable regimens in control groups. Meta-analyses were conducted to pool event rates and risk ratios (RRs). Subgroup analyses and meta-regression were performed to identify potential sources of heterogeneity.Results Data from 12 studies involving 1902 DR-TB patients across 11 countries were analysed. The pooled TSR was 83% (95% CI 77% to 89%), with mortality, treatment failure and loss to follow-up (LTFU) rates of 5% (3–8), 4% (2–6) and 4% (2–6), respectively. Subgroup analyses showed no significant differences in TSR by DR-TB type or HIV status. The incidence rate of SAE was 19% (13–24), with prolonged corrected QT interval (QTc) in 5% (2–8) of cases. Compared with the control regimens, all-oral Bdq-based shorter regimens significantly improved treatment success (RR 1.22, 1.04–1.43) but reduced mortality (RR 0.73, 0.69–0.99), treatment failure (RR 0.33, 0.32–0.62) and QTc prolongation (RR 0.39, 0.21–0.73).Conclusions All-oral Bdq-based shorter regimens have improved treatment outcomes and significantly advanced DR-TB management. We urge policymakers, clinicians and stakeholders to expand access to and expedite the implementation of these regimens.